New-onset super refractory status epilepticus: A case-series. (February 2020) - Aurangzeb, Sidra; Prisco, Lara; Adcock, Jane; Speirs, Mahiri; Raby, Simon; Westbrook, Jon; Sen, Arjune
Highlights: Some cases of NORSE are due to autoimmune aetiology. The disorder has significant morbidity and mortality but good outcome remains possible even in cases with very prolonged ICU stays. Abstract: Introduction: Literature on New-Onset Refractory Status Epilepticus (NORSE) is scarce and management is guided mainly by retrospective reports, short case series or expert opinions. We aimed to add to the pool of the available data by retrospectively reviewing seven cases of NORSE cases admitted to our hospital over the last five years between January 2014 and March 2019. Methods: Fully anonymised data from medical charts, EEG reports, imaging reports, laboratory test results, types of antiepileptic medications, intravenous anaesthetic therapy, and immune therapies received was collected, along with response to treatment, length of hospital stay and outcome at discharge. Results: The mean age was 43.5 ± 23.8 years (range 18–75) and three patients were females. Prodromal symptoms consisted mainly of fever (4/7), headache (4/7) and self terminating seizures (7/7), before presenting with status epilepticus. Initial imaging findings were abnormal in 3/7 and CSF analysis in 3/7. All patients underwent intermittent EEG recordings, mainly for titration or tapering of the anaesthetic agents, with the initial goal of achieving burst suppression and cessation of electrographic seizures. Our index case spent the longest time in therapeutic burst suppression (102 days) and remained on thiopentone for 214 days. The mean duration of NICU stay was 88 ± 85.4 days (range 4–225 days) while the mean duration of hospital stay was 113.8 ± 111.2 days (range 17–292). Conclusions: The management of patients with NORSE remains challenging, often requiring multiple intravenous anaesthetic treatments, leading to complicated and prolonged hospital and intensive care unit stays but good outcome remains possible.